Towards effective worker grievance handling: some reflections - Opatha, H.H.D.N.P.; Ismail, Zakaria (Universiti Utara Malaysia, 2001)
This paper seeks to provide a comprehension of Worker Grievance Handling(WGH) which is a crucial aspect of human resource management and industrial relations in an industrializing country in the new millennium. WGH is meant for accepting and resolving grievances of workers with the purpose of enhancing industrial peace. Effective WGH has its unique significance for good labour relations, worker motivation and worker productivity. The paper has its main area of focus on three key dimensions of the WGH, namely grievances policy, grievance procedure and grievance practice. As an agenda of action for efective WGH, a few suggestions are also given.The paper may be of assistance to firms in a newly industrialized country in enhancing their worker grievances handling ang also to those who are interested in undnrtanding WGH for research purposes.